2015
DOI: 10.1021/acs.jcim.5b00338
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the Optimal Rigid Receptor for Docking and Scoring in the CSAR 2013/2014 Experiment

Abstract: The 2013/2014 Community Structure–Activity Resource (CSAR) challenge was designed to prospectively validate advancement in the field of docking and scoring receptor–small molecule interactions. Purely computational methods have been found to be quite limiting. Thus, the challenges assessed methods that combined both experimental data and computational approaches. Here, we describe our contribution to solve three important challenges in rational drug discovery: rank-ordering protein primary sequences based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…As reported, our approach of using “close” methods for pose predictions, where all available crystallographic information (mostly co-crystals) is used, yielded the most accurate poses in the community-wide experiment for both targets. Consistent with our earlier work [29], align-close was particularly robust for both flexible targets. Although dock-close predicted better-docked poses to the rather tight pocket of HSP90, the same method failed predicting good poses in the much larger binding site of MAP4K4.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As reported, our approach of using “close” methods for pose predictions, where all available crystallographic information (mostly co-crystals) is used, yielded the most accurate poses in the community-wide experiment for both targets. Consistent with our earlier work [29], align-close was particularly robust for both flexible targets. Although dock-close predicted better-docked poses to the rather tight pocket of HSP90, the same method failed predicting good poses in the much larger binding site of MAP4K4.…”
Section: Discussionsupporting
confidence: 91%
“…We participated in the 2013/14 CSAR challenge that involved rank-ordering compounds to homology models of the receptors with a given protein primary sequence, identifying close-to-native bound conformations out of a set of decoy poses, and rank-ordering the affinity of sets of congeneric compounds to a given protein. Our predictions were among the best in the field [29, 30]. We showed that the most significant contribution to a meaningful enrichment of native-like models was the identification of the best receptor structure for docking and scoring.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Values of Baumgartner et al . 49 were computed from Figure 6 of their paper. Values of Matiny et a l. 46 were computed from R 2 values in Table 3 of their paper.…”
Section: Resultsmentioning
confidence: 99%